2023
DOI: 10.1002/ppap.202200234
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatocellular carcinoma with in situ generated plasma‐activated air‐driven water mist

Abstract: Since the development of cold atmospheric plasma (CAP), substantial and significant usage of CAP applications was introduced in medicine. Here, we developed two combined sources of plasma to produce in situ plasma‐activated air‐driven water mist (PAAWM). The first is generated using air as a feed gas, while the second is plasma‐activated water generated by the ignition of plasma within the air‐driven water mist. Both contribute to the plasma jet generation of PAAWM. The antitumor efficacy of PAAWM was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Saadaway et al described a similar approach to deliver therapeutic doses of PAW mist. They termed their technique as plasma-activated air-driven water mist (PAAWM) and showed that the resultant mist was effective against multiple cancer cell lines in an in vitro study [133].…”
Section: Interactions Of Plasma With Liquidsmentioning
confidence: 99%
“…Saadaway et al described a similar approach to deliver therapeutic doses of PAW mist. They termed their technique as plasma-activated air-driven water mist (PAAWM) and showed that the resultant mist was effective against multiple cancer cell lines in an in vitro study [133].…”
Section: Interactions Of Plasma With Liquidsmentioning
confidence: 99%
“…Another popular application of cold plasmas and plasma‐treated media is in the field of oncology as an anticancer treatment strategy, as shown in the paper by Saadawy et al [ 8 ] This paper presents a novel approach for the treatment of hepatocellular carcinoma using plasma‐treated air‐driven water mist. The findings highlight plasma‐generated reactive species to induce selective cancer cell death, providing a promising avenue for noninvasive cancer therapies.…”
mentioning
confidence: 99%